Factor Analysis of the Influence of supply chain management on the Economic Dynamics of the Region - Marat Rashitovich Safiullin; Leonid Alekseevich Elshin; Dinara Lenarovna Kurbangalieva (International Journal of Supply Chain Management, 2020)
Abstract— The main goal of the study is to develop methodological approaches to a formalized assessment of the impact of supply chain management and its individual components on the development parameters of key macroeconomic indicators of a region (for example, investment in fixed assets). Testing the proposed research algorithms made it possible to substantiate a high level of reputation significance in the formation of regional economic growth. The implemented factor analysis provided an identification of the impact of the individual sub-indices under consideration, which form the integral value of the region’s supply chain management, on investment activation processes. The Republic of Tatarstan acts as an object of the study. The subject of the research is a methodological toolkit for conducting factor analysis and assessing the impact of the region's reputation on the parameters and dynamics of investment processes. A key feature of the study is the proposed version of constructing a series of regression equations, where the region’s supply chain management index is one of the exogenous parameters. The use of elimination methods has allowed the formation of a factor analysis focused on the impact of the individual components of the index under study on investment processes. On the basis of the developed methodology for the formalized assessment of the region’s supply chain management, the authors have built models that assess the level of influence of sub-indices that form the basis for an integrated assessment of the territory’s reputation on investment dynamics. It is advisable to use the developed methodological approaches when developing new models of economic growth under conditions of increased importance and the role of intangible production factors. According to the results of the study, the influence of each of the sub-indices under consideration on the dynamics of investment in fixed assets of the region was established, which made it possible to justify and formulate measures of state influence on the corresponding functional directions of the regional socio-economic system.